2017
DOI: 10.1155/2017/6181405
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Agreement of Central Corneal Thickness and Keratometry Measurements between Four Different Devices

Abstract: Background. To estimate repeatability and comparability of central corneal thickness (CCT) and keratometry measurements obtained by four different devices in healthy eyes. Methods. Fifty-five healthy eyes from 55 volunteers were enrolled in this study. CCT (IOLMaster 700, Pentacam HR, and Cirrus HD-OCT) and keratometry readings (IOLMaster 700, Pentacam HR, and iDesign) were measured. For statistical analysis, the corneal spherocylinder was converted into power vectors (J0, J45). Repeatability was assessed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…Chang et al 4 compared the astigmatic measurements obtained with Pentacam and IOL Master and did not find statistically significant differences between devices in the measurement of the magnitude of corneal astigmatism. Kiraly et al 31 reported significantly higher values of corneal J 0 with Pentacam compared to IOL-Master, with no significant differences between devices for J 45 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chang et al 4 compared the astigmatic measurements obtained with Pentacam and IOL Master and did not find statistically significant differences between devices in the measurement of the magnitude of corneal astigmatism. Kiraly et al 31 reported significantly higher values of corneal J 0 with Pentacam compared to IOL-Master, with no significant differences between devices for J 45 .…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, the absolute value of this power vector component was higher when measured with IOL-Master compared to the Pentacam system. Comparisons between Cassini versus Pentacam, 10,30 and also between Pentacam and IOL-Master 4,31 have been previously performed. Apparently contradictory conclusions/results have been reported, although the ranges of agreement are consistent with those obtained in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Revo NX is the latter type. Contrary to most OCT machines with add on lens that measure only anterior curvature, [6] it is cable of generating anterior and posterior corneal surface maps with respective keratometry. Measuring posterior corneal power is vital in keratoconic patients and in IOL calculation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kiraly et al . used Cirrus HD-OCT 5-line raster mode as well as Pentacam HR to estimate repeatability and comparability of the CCT measurements [ 34 ]. The mean difference between these methods was shown to be 11.44 µm, which was comparable to our maximum reported mean difference of 13.5 µm.…”
Section: Discussionmentioning
confidence: 99%